Effects of Indoor Air Curtain and Fan on Cross-Infection Risk for a Space with Displacement Ventilation - Robinson Austin; Zhai Zhiqiang (John) (E3S Web of Conferences, 2023)
Air curtain is an effective control for separating air spaces and reducing the cross-transfer of air, heat, and contaminant between different zones. Studies show that displacement ventilation is better for indoor air quality than mixed ventilation. However, displacement ventilation may be susceptible to a phenomenon called lock-up, whereby contaminants are held in a lower stratified portion of the space and increase infection potential. This study investigates whether indoor air curtain and circulation fan can reduce the lock-up phenomenon for spaces with displacement ventilation and thus reduce infection risk across the breathing zone. Specially, numerical test is conducted to explore if a side-wall diffuser-integrated vertical slot air curtain would be sufficient for reducing infection risk. Additionally, circulation fans above the occupants are applied to explore if they would reduce the lock-up phenomenon. The conclusions are that neither a side air curtain slot nor circulation fans is/are adequate to reduce infection risk. In fact, all methods tested increased infection risk. This increase in infection risk is contrary to previous research and is due to changing air flow patterns throughout the space that disrupted thermal plumes and created contaminant leakage from one side of the room to the other. Circulation fans provided the promising results while further optimization should be conducted in terms of the ideal quantity, location, flow rate, orientation, and size of fans throughout a given space.